Gender, Volunteerism and Military Hospitals: War Nurses, Educators and Philanthropists of the Nineteenth-Century - Irene Kamberidou (The 14th ERGOMAS Conference: Military and Society: New Models for New Challenges, Working Group “Gender and the Military”, 2017)
Thousands of European and American women provided their services, lobbied, raised funds, food supplies and clothing to support the Greek Revolution.  Along with the relief activities of the 1820’s and 1830’s, the great interest in Greece produced a strong desire to send teachers and missionaries to Greece in Bondage.  Women’s 19th century accounts examine the position of the subjugated Greeks in the Aegean Islands and Asia Minor. European and American women—educators and philanthropists—worked for the advancement of female education. They even established schools for the preservation of Hellenic cultural heritage. This paper focuses on the first-hand accounts of 19th century European aristocratic and middle-class women volunteers, and specifically their social contribution during the Crimean War (1853-1856), when the English and French colonial experience encouraged female volunteerism. It spotlights the social service provided by English, French and German nurses and philanthropists—as agents of social change—who cared for the soldiers in the hospitals of Constantinople and its environs, concluding with their invaluable recommendations. The female accounts describe the British military and naval hospitals, hospital huts, nurses duties and difficulties confronted (1,500 patients per 3 volunteers); the Women’s Hospital; the French hospitals; the French military system; the Sisters of Mercy; the Sisters of Charity; the women who followed their husbands to war, including the destitute wives and babies of the English soldiers. Astonishing are the accounts concerning the degrading social status of the English soldier’s wife as opposed to the respect and protection enjoyed by the French soldier’s wife.